Comparative efficacy of antiviral therapy in preventing vertical transmission of hepatitis B: a network meta‐analysis. (1st October 2015) - Njei, Basile; Gupta, Neil; Ewelukwa, Oforbuike; Ditah, Ivo; Foma, Munoh; Lim, Joseph K.
Abstract: Background & Aims: Antiviral drugs are safe and effective in the third trimester to prevent intrauterine transmission of hepatitis B virus, and are recommended for hepatitis B virus (HBV) infected gravid mothers (between weeks 28 and 32) with high viral load, followed by postnatal hepatitis B immunization in the newborn. We estimated the comparative efficacy of antiviral drugs for prevention of vertical transmission of HBV, through a network meta‐analysis of clinical trials. Methods: We conducted a comprehensive search of MEDLINE, EMBASE and published proceedings from major liver meetings from January 1980 to November 2014. We conducted pair‐wise meta‐analyses and Bayesian framework using Markov chain Monte Carlo methods, combining direct and indirect evidence for any given pair of treatments. Results: Seventeen clinical trials involving 2764 newborns of hepatitis B surface antigen seropositive mothers were eligible for analysis. There were no clinical trials involving tenofovir or entecavir. On pair‐wise meta‐analyses, telbivudine (hazard ratio, HR 0.12, 95% confidence interval (CI) 0.04–0.37; I 2 = 0%), and Lamivudine (HR 0.40, 95% CI 0.24–0.65; I 2 = 0%), were more effective than placebo in reducing vertical transmission of HBV in high viremic hepatitis B e antigen (HBeAg)‐positive chronic Hepatitis B Chinese patients. Sensitivity analyses limited to studies with HBeAg seropositive mothers revealed similar results. Conclusions: Based on a Bayesian network meta‐analysis of clinical trials, combining direct and indirect treatment comparisons, telbivudine appears to be more effective than Lamivudine for preventing vertical transmission of HBV infection. Trials assessing the efficacy of tenofovir or entecavir compared to placebo or other antiviral drugs are lacking.